The relationship between family structure and exclusive breastfeeding prevalence in Nicaragua - Espinoza Henry (Instituto Nacional de Salud Pública, 2002)
Objective. To examine the relationship between family structure and the prevalence of exclusive breastfeeding (EBF) in Nicaragua. Material and Methods. A subset of the Nicaraguan Demographic and Health Survey conducted in 1998 was obtained by selecting all last-born infants less than 4 months old at the time of the survey. Weighted chi-squared and multivariate logistic regression analyses were used to examine the association. Results. Interviewee women heads of household and interviewee women whose husbands were the heads of the household had a significantly lower prevalence of EBF. Exposure to the health care system was not related to EBF. Conclusions. New approaches are needed to promote that men support women's decisions to breastfeed. Health institutions should effectively communicate the benefits of breastfeeding on both the mother and the child.